2016
DOI: 10.1002/jpln.201600079
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved and colloidal phosphorus fluxes in forest ecosystems—an almost blind spot in ecosystem research

Abstract: Understanding and quantification of phosphorus (P) fluxes are key requirements for predictions of future forest ecosystems changes as well as for transferring lessons learned from natural ecosystems to croplands and plantations. This review summarizes and evaluates the recent knowledge on mechanisms, magnitude, and relevance by which dissolved and colloidal inorganic and organic P forms can be translocated within or exported from forest ecosystems. Attention is paid to hydrological pathways of P losses at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
109
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 141 publications
(118 citation statements)
references
References 154 publications
(185 reference statements)
7
109
2
Order By: Relevance
“…Some of the relevant P fluxes are hard to quantify (Bol et al 2016) and not yet available at the study sites. However, the different P nutrition strategies can modify the studied P characteristics of the ecosystems as well as other ecosystem properties.…”
Section: Indicators For P Acquisition and P Recyclingmentioning
confidence: 99%
“…Some of the relevant P fluxes are hard to quantify (Bol et al 2016) and not yet available at the study sites. However, the different P nutrition strategies can modify the studied P characteristics of the ecosystems as well as other ecosystem properties.…”
Section: Indicators For P Acquisition and P Recyclingmentioning
confidence: 99%
“…At low pH, P is bound to Fe and Al oxides, while at high pH, P is typically unavailable because of complex formation with Ca. P availability is thus maximal at intermediate pH (Chapin et al, 2002;Bol et al, 2016), while enhanced leaching of base cations occurs in acidic soils, thus lowering the amount of total 55 exchangeable bases (TEB = cation equivalent of summed K, Ca, Mg and Na - IIASA and FAO, 2012). Hence, unlike temperature or precipitation, nutrient availability cannot be assessed by measuring one single parameter.…”
Section: Introductionmentioning
confidence: 99%
“…The highest concentrations were measured during events in summer and fall after long dry periods with little or no precipitation. The increased concentration of TP-P during the summer and fall seasons indicates that during dry periods P accumulates in the soil, which then is flushed by precipitation water during rain events [6]. Recent studies have demonstrated that dry and rewetting cycles, which occur more often during summer and fall seasons, increase the export of P from the organic layers and upper mineral horizons [26].…”
Section: Seasonmentioning
confidence: 99%
“…At the landscape scale, P is exported mainly via streamflow either in solution or as a particulate, and in either organic or inorganic forms [3][4][5]. The magnitude and dynamics of P export fluxes from forests are determined by the availability of P from the geologic parent materials as well as from the internal cycling of P within the forest ecosystem [1,6]. In forest soils, nutrients can be easily exported via preferential flow pathways, such as macropores or at the interface between organic and mineral soil layers [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation